2022
DOI: 10.3390/met12091545
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Noise Analysis of the X70 Pipeline Steel under Stress Conditions Using Symmetrical and Asymmetrical Electrode Systems

Abstract: In this work, electrochemical monitoring of stress corrosion cracking (SCC) behavior of a X70 steel in acidic synthetic soil solution during the slow strain rate test (SSRT) was performed by electrochemical noise (EN) using the conventional arrangement of symmetrical electrodes and electrochemical emission spectroscopy (EES) using the asymmetrical arrangement replacing the second working electrode for a platinum micro-cathode. The statistical method, fast Fourier transform, and discrete wavelet transform were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The low energy is related to passive systems, as is presented in Figure 6a for all samples except Ti-6Al-4V anodized in KOH and Figure 6b for all samples. Authors such as Carmona-Hernandez et al [65] suggest that the discontinuous process is like metastable pitting, relating that with this project, the different process is caused by a non-homogenous surface that induces the accumulation of energy in the first crystals of Ti-6Al-4V anodized in KOH. The TiO 2 generated on the surface was stable enough for the rest of the samples, and the nucleation of the localized process did not occur in this experiment's parameters.…”
Section: Sem After Corrosionmentioning
confidence: 67%
“…The low energy is related to passive systems, as is presented in Figure 6a for all samples except Ti-6Al-4V anodized in KOH and Figure 6b for all samples. Authors such as Carmona-Hernandez et al [65] suggest that the discontinuous process is like metastable pitting, relating that with this project, the different process is caused by a non-homogenous surface that induces the accumulation of energy in the first crystals of Ti-6Al-4V anodized in KOH. The TiO 2 generated on the surface was stable enough for the rest of the samples, and the nucleation of the localized process did not occur in this experiment's parameters.…”
Section: Sem After Corrosionmentioning
confidence: 67%
“…Those cracks can either proceed along grain boundaries (intergranular) or through the grains (transgranular). [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…), are usually applied as key parameters to detect localized corrosion [48,56]. This is also applicable to a complex corrosive mechanism such as SCC [18]. Details of the main statistical parameter of the ENC and ENP time series investigated in this paper are reported in [14]; however, usually it is required to take a multiple variable approach on EN features, e.g., by using a neural network method [14], to discriminate the fundamental parameters and their correlation during the different and synergistic phases of the process.…”
Section: Time Domain Analysismentioning
confidence: 99%
“…In this concern, studies performed on stainless steel under various conditions [15,16] showed that on SCC tests, it may be feasible to quantify electrochemical current and voltage noise variations caused by the cyclical activation and propagation of cracks. In a lot of research activities [17][18][19], hydrogen embrittlement and the impact of the related evolved hydrogen bubbles on the EN transient was accurately investigated.…”
Section: Introductionmentioning
confidence: 99%